A reconfiguração do campo da pós-graduação e da pesquisa na universidade à luz de mudanças jurídicopolíticas decorrentes das políticas de inovação no Brasil: o caso UFU - Sacramento, Leonardo Freitas (Universidade Federal de São Carlos, 2011)
The aim of this study was the analysis of the influence of legal, political and institutional mediations in some changes in the post-graduation course of the Federal University of Uberlandia (UFU).We sought to elucidate, through the analysis of various documents (laws, ordinances, resolutions, decrees, edicts, Postgraduate National Plans, etc.) and data from Brazilian post-graduate courses at FAPEMIG and UFU, the ways in which the guidelines induced by the legal-political changes of the national postgraduation system and by the national and Minas Gerais State innovations which are being framed in the UFU. We analyzed the relevance of the laws of the university reform in the consolidation of a new evaluation paradigm of the teacher-researcher, who established and legitimized a heteronomous management based on academic productivism. It was argued that such reforms are in line to the foundations of the State Reform and the adjustment of the Brazilian economy to mundialization of capital, the reconfiguration of the practices and culture in the university, with the aim of meeting the demands of the business sector and the needs and interests of productive capital, were also mentioned. We analyzed the importance of the role of national bodies to encourage research and evaluation, such as CNPq, FINEP and CAPES, as well as organs of the State of Minas Gerais, FAPEMIG particularly, which were fundamental to the institution of changes in the postgraduate studies at UFU, particularly for the implementation of a policy of innovation and progressive dissemination of research and applied knowledge of predominantly instrumental character. It was felt that innovation and its diffusion take place through public-private partnerships and the creation of institutional structures that enable the commercialization of knowledge and products that potentially could improve the production of goods with high added value. It was considered that the documents analyzed were necessary mediations to create university instances, which, in turn, have taken shape and are configured as articulating the relationship among teacher-researchers, FAPEMIG and market, especially the Center for Innovation Intellect/UFU, the Foundation for University Support and Incubation Centre for Entrepreneurial Activities. It was concluded that the restructuring of research practices and the creation of these new institutional structures, which enable the spreading of the knowledge from them derived, tend to promote and intensify the exchange between university-enterprise, since they would have been predominantly driven by the scope of making UFU more adjusted to private capital.
Keywords: Universidades e faculdades - pós-graduação; Universidade Federal de Uberlândia; Mundialização do capital; Pesquisa; Inovação; Ciência e tecnologia; University of Uberlandia; Mundialization of capital; Research and innovation; Science and technology; CIENCIAS HUMANAS::EDUCACAO